HUBUNGAN PENGGUNAAN KONTRASEPSI HORMONAL DENGAN OBESITAS PADA WANITA USIA SUBUR (WUS) DI PUSKESMAS WAWONASA KECAMATAN SINGKIL MANADO - Hasan, Mulyana (e-Biomedik, 2013)
ABSTRACT Obesity is caused by several factors, one of them is the use of contraception in particular the use of hormonal contraceptives that its use can cause various side effects such as changes in body weight-acceptor. The research aims to determine the relation of hormonal contraceptive use with obesity in women of childbearing age (WUS) of public health insurance participants in the Wawonasa clinic. This study is an Observational Analytics with cross-sectional and conducted in Wawonasa clinic Singkil district Manado with data collection in the form of identity, body weight, height, and direct interviews with the respondents. The total sample of 77 respondents. The respondents who use hormonal contraception are 49 respondents while the respondents who did not use contraception are 28 respondents. The respondents who use hormonal contraception and were obese are 22 respondents. Conclusion: The type of contraception most widely used by women of childbearing age at Puskesmas Wawonasa is hormonal contraceptives and there is no relationship between the use of contraception with obesity in women of childbearing age at Wawonasa clinic. Keywords: hormonal contraceptives, obesity, women of childbearing age ABSTRAK Obesitas disebabkan oleh beberapa faktor, salah satunya penggunaan kontrasepsi khususnya kontrasepsi hormonal yang penggunaannya dapat menimbulkan berbagai efek samping seperti perubahan berat-badan akseptor. Penelitian bertujuan untuk mengetahui hubungan penggunaan kontrasepsi dengan obesitas pada wanita usia subur (WUS) peserta jamkesmas di Puskesmas Wawonasa. Penelitian ini bersifat Observasional Analitik dengan pendekatan cross-sectional dan dilakukan di Puskesmas Wawonasa Kecamatan Singkil Manado dengan pengambilan data berupa identitas, berat badan, tinggi badan, dan wawancara langsung terhadap responden. Jumlah sampel sebanyak 77 responden. Jumlah responden yang menggunakan kontrasepsi hormonal sebanyak 49 responden sedangkan yang tidak menggunakan kontrasepsi berjumlah 28 responden. Jumlah responden yang menggunakan kontrasepsi hormonal dan mengalami obesitas sebanyak 22 responden. Kesimpulan: Jenis kontrasepsi yang paling banyak digunakan oleh wanita usia subur Puskesmas Wawonasa adalah kontrasepsi hormonal dan tidak terdapat hubungan antara penggunaan kontrasepsi dengan obesitas pada wanita usia subur puskesmas Wawonasa. Kata kunci: kontrasepsi hormonal, obesitas, wanita usia subur